Central Banks and Profitability: A Systematic Literature Review - Mega Fauziah; Adler Haymans Manurung; Roy Sembel (DINASTI RESEARCH, 2023)
Abstract: Although the topic of central bank has been studied mainly in relation to the role of monetary authority and financial system regulator, the topic of central bank profit has not yet received much attention because it is difficult to observe central bank profitability due to their nature as public institutions. The review provides evidence from 22 documents, which are then classified into five central bank profitability themes: independence, monetary policy effectiveness, competition, operations and risk, and public finance. We conclude that central bank profitability can be a research agenda as profitability can be perceived as central banks’ financial strength to conduct their responsibility and to maintain their credibility.